2017
DOI: 10.1016/j.jpainsymman.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Physical Function Profiles in Older Adults Receiving Cancer Chemotherapy

Abstract: Context While physical function is an important patient outcome, little is known about changes in physical function in older adults receiving chemotherapy (CTX). Objectives Identify subgroups of older patients based on changes in their level of physical function; determine which demographic and clinical characteristics were associated with subgroup membership; and determine if these subgroups differed on quality of life (QOL) outcomes. Methods Latent profile analysis (LPA) was used to identify groups of ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…A recent study also identified three patient groups with distinct trajectories of patient-reported physical function, i.e. poor, intermediate, and good [38], though these were all stable. Supporting our finding, depression, and lower physical activity were among the main characteristics within the poor group.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A recent study also identified three patient groups with distinct trajectories of patient-reported physical function, i.e. poor, intermediate, and good [38], though these were all stable. Supporting our finding, depression, and lower physical activity were among the main characteristics within the poor group.…”
Section: Discussionmentioning
confidence: 94%
“…Secondly, the choice of assessment tools may have impacted our results. This particularly applies to our comorbidity assessment, since comorbidity has been found to affect older patients' physical function and QoL in other studies using more comprehensive assessments than the OARS [38,54]. Thirdly, the multitude of factors included in our analyses may introduce uncertainties, and the exploratory analysis related to PF trajectories should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…malnutrition, etc. ), cancer and its treatment confer a range of effects which reduce quality of life (QoL) [10]. One recent study found that nearly two-thirds of older people assessed in hospital had at least one tissue loss syndrome (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is helpful for improving survival, while it may also cause adverse consequences in quality of life (QOL; Brahmer et al., ; Quinten et al., ; Udupa, Rajendranath, & Sagar, ; Zietarska, Krawczyk‐Lipiec, Kraj, Zaucha, & Malgorzewicz, ), fatigue (Levkovich, Cohen, & Karkabi, ; Sette et al., ; Vardy et al., ), depression (Bergerot, Mitchell, Ashing, & Kim, ; Bhattacharyya, Bhattacherjee, Mandal, & Das, ; Zhang, Zhou, Feng, Xu, & Zeng, ), anxiety (Charalambous, Kaite, Charalambous, Tistsi, & Kouta, ; Papadopoulou et al., ), body composition (Palmela et al., ; Rier et al., ), and physical functioning (Miaskowski et al., ; Timilshina, Breunis, Tomlinson, Brandwein, & Alibhai, ). Many non‐pharmacological interventions are proposed to prevent or reduce these adverse consequences (Can, Erol, Aydiner, & Topuz, ) and accumulating evidence implies that exercise may effectively reduce side effects caused by chemotherapy (Meneses‐Echavez, Gonzalez‐Jimenez, & Ramirez‐Velez, ).…”
Section: Introductionmentioning
confidence: 99%